2020
DOI: 10.3390/brainsci10010044
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Mechanisms Involved in Sensory Gating Disruption Induced by (±)-3,4-Methylene- Dioxymethamphetamine (MDMA): Relevance to Schizophrenia

Abstract: Sensory gating deficits have been demonstrated in schizophrenia, but the mechanisms involved remain unclear. In the present study, we used disruption of paired-pulse gating of evoked potentials in rats by the administration of (±)-3,4-methylene-dioxymethamphetamine (MDMA) to study serotonergic and dopaminergic mechanisms involved in auditory sensory gating deficits. Male Sprague-Dawley rats were instrumented with cortical surface electrodes to record evoked potential changes in response to pairs of 85dB tones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…This gating could serve to reduce sensory input during 'internal 'hippocampal memory processing, effectively decreasing potential interference that would disrupt memory consolidation (44,45). While the mechanism of 5-HT's effect on long-range neural synchrony is not yet clear, it has been shown that 5-HT can alter sensory gating dependent on communication between the thalamus and hippocampus (46). Furthermore, a recent study showed that type 2 dentate spikes (DS2s) in the hippocampus constitute substates of high arousal within immobility periods (47).…”
Section: Discussionmentioning
confidence: 99%
“…This gating could serve to reduce sensory input during 'internal 'hippocampal memory processing, effectively decreasing potential interference that would disrupt memory consolidation (44,45). While the mechanism of 5-HT's effect on long-range neural synchrony is not yet clear, it has been shown that 5-HT can alter sensory gating dependent on communication between the thalamus and hippocampus (46). Furthermore, a recent study showed that type 2 dentate spikes (DS2s) in the hippocampus constitute substates of high arousal within immobility periods (47).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MDMA can affect the perception of sound. Animal models show that auditory sensory gating is directly affected during MDMA use ( 45 ), and that this action depends on the serotonin receptor 5-HT2A ( 46 ). Since auditory gating may also be affected in misophonia ( 24 ), it would be of interest to see if MDMA administration could counteract these auditory gating abnormalities, but this remains to be examined.…”
Section: Proposed Mdma Effects On Relevant Misophonia Symptomsmentioning
confidence: 99%
“…MDMA use has been previously shown to induce psychosis in single case studies (20)(21)(22). In rats MDMA has been shown to disrupt mechanisms of auditory sensory gating via its involvement in both dopaminergic and serotonergic pathways (23,24). Sensory gating is a form of information processing where irrelevant stimuli are being ignored and is being hypothesized to be deficient in patients suffering from PDs (25).…”
Section: Introductionmentioning
confidence: 99%